Pitfalls of delaying the diagnosis of hereditary haemorrhagic telangiectasia. Issue 2 (October 2020) - Major, Tamás; Csobay-Novák, Csaba; Gindele, Réka; Szabó, Zsuzsanna; Bora, László; Jóni, Natália; Rácz, Tamás; Karosi, Tamás; Bereczky, Zsuzsanna
Hereditary haemorrhagic telangiectasia (HHT; Osler–Weber–Rendu disease) is an autosomal dominant vascular disease characterized by nosebleeds, mucocutaneous telangiectases, visceral arteriovenous malformations (AVM) and a first-degree relative with HHT. Diagnosis is definite if three or four criteria are present. This case report describes a 19-year-old male with incidentally detected polycythaemia and an associated soft-tissue opacity over the left lower lobe on his frontal chest radiogram. He had experienced dyspnoea on exertion since infancy and clubbing at physical examination. Polycythaemia vera, chronic obstructive pulmonary disease, sleep apnoea and cyanotic congenital heart disease were excluded. Chest computed tomography (CT) was initially refused by the patient, but 3 years later he presented with severe epistaxis. Considering the unvarying soft tissue mass and erythrocytosis, an HHT-associated pulmonary AVM (PAVM) was eventually confirmed by chest CT. A pathogenic family-specific ENG c.817-2 A>C mutation was detected in the patient. The large PAVM was successfully treated using AMPLATZER™ vascular plug embolization. A combination of the multisystemic nature of his symptoms, the age-related penetrance of HHT symptoms and insufficient patient compliance delayed the diagnosis of HHT in this current case.